Isolation and characterization of cDNA encoding the alpha subunit of Cap Z(36/32), an actin-capping protein from the Z line of skeletal muscle. - Casella, J F (1989)
cDNA encoding the alpha chain of Cap Z has been isolated by screening a lambda gt11 library with affinity-purified antibodies. A single cDNA insert (designated CE2) of 2153 base pairs (bp) contains an open reading frame of 836 bp, which is incomplete at its 5' end. The technique of "rapid amplification of cDNA ends" has been used to extend the 5' end of this open reading frame to a potential transcription initiation site that is preceded by 320 bp of an apparently untranslated region. The protein predicted by the resulting nucleotide sequence has a Mr of 32,960 and contains four regions that show close homology with four alpha-chymotryptic digestion fragments of the alpha chain. The amino acid composition of the alpha chain of Cap Z and the predicted protein are also similar. Northern blot analysis of whole chicken embryos shows two mRNA species of 1.9 and 2.4 kilobases, respectively, that hybridize with CE2. Three potential polyadenylylation signals in two regions of CE2 460 bp apart are identified, suggesting that the two messages may result from the use of alternative polyadenylylation sites. Comparison of the sequence data with that of other known actin-capping and severing proteins shows no significant homologies, suggesting that Cap Z may be a member of a unique group of capping, nonsevering proteins.